Alterations in cellular metabolome after pharmacological inhibition of Notch in glioblastoma cells. Issue 5 (13th October 2015) - Kahlert, Ulf D.; Cheng, Menglin; Koch, Katharina; Marchionni, Luigi; Fan, Xing; Raabe, Eric H.; Maciaczyk, Jarek; Glunde, Kristine; Eberhart, Charles G.
Abstract : Notch signaling can promote tumorigenesis in the nervous system and plays important roles in stem‐like cancer cells. However, little is known about how Notch inhibition might alter tumor metabolism, particularly in lesions arising in the brain. The gamma‐secretase inhibitor MRK003 was used to treat glioblastoma neurospheres, and they were subdivided into sensitive and insensitive groups in terms of canonical Notch target response. Global metabolomes were then examined using proton magnetic resonance spectroscopy, and changes in intracellular concentration of various metabolites identified which correlate with Notch inhibition. Reductions in glutamate were verified by oxidation‐based colorimetric assays. Interestingly, the alkylating chemotherapeutic agent temozolomide, the mTOR‐inhibitor MLN0128, and the WNT inhibitor LGK974 did not reduce glutamate levels, suggesting that changes to this metabolite might reflect specific downstream effects of Notch blockade in gliomas rather than general sequelae of tumor growth inhibition. Global and targeted expression analyses revealed that multiple genes important in glutamate homeostasis, including glutaminase, are dysregulated after Notch inhibition. Treatment with an allosteric inhibitor of glutaminase, compound 968, could slow glioblastoma growth, and Notch inhibition may act at least in part by regulating glutaminase and glutamate. Abstract : What's new? Glutamate metabolism may play a key role in brain tumor growth. These authors investigated the effects of blocking Notch, an important developmental pathway for some stem cells. They tested the change in levels of various metabolites in brain tumor cells when Notch was blocked. They found a drop in glutamate levels, a change that did not occur when they blocked Notch in human neural stem cells nor did they observe this loss of glutamate when they suppressed other signaling pathways. Perhaps, the authors suggest, Notch regulates tumor growth via glutamate metabolism, and hindering glutaminase could be a useful therapeutic avenue.